The Influence of Geographical Conditions on Flood Disasters in Tunggul Irang Ilir Village - Rabi Yati; Ersis Warmansyah Abbas; Rusmaniah Rusmaniah; Muhammad Rezky Noor Handy; Mutiani Mutiani (The Innovation of Social Studies Journal, 2024)
Natural disasters such as floods can be caused by both natural and non-natural factors, such as human activities. The convergence of human activities, static environmental conditions, and dynamic natural phenomena can result in flooding. Static natural elements (topography, rivers, and geographical conditions) and dynamic natural factors (rainfall, tidal currents, land subsidence, and river sedimentation) are the causes of flooding disasters. Tunggul Irang Ilir Village is a village located in the Martapura District of Banjar Regency that experiences flooding every year. It is known that the floods in Tunggul Irang Ilir Village involve several factors, primarily due to the village's geographic conditions, making the area prone to flooding disasters. Therefore, research is conducted on the geographical conditions' impact on flooding in Tunggul Irang Ilir Village to understand the village's geographical conditions and their influence on the floods that occur annually. Using a qualitative descriptive research method, data is collected through documentation, interviews, and observation. Data analysis involves stages such as data reduction, data presentation, conclusion drawing, and verification. This research employs data triangulation, technique triangulation, and time triangulation to test validity. The results of the research indicate that geographic conditions, including the village's location, climate, weather, low land topography, and Martapura River overflow, are factors causing floods in Tunggul Irang Ilir Village.